2019
DOI: 10.1136/annrheumdis-2018-214786
|View full text |Cite
|
Sign up to set email alerts
|

CircSERPINE2 protects against osteoarthritis by targeting miR-1271 and ETS-related gene

Abstract: ObjectivesCircular RNAs (circRNA) expression aberration has been identified in various human diseases. In this study, we investigated whether circRNAs could act as competing endogenous RNAs to regulate the pathological process of osteoarthritis (OA).MethodsCircRNA deep sequencing was performed to the expression of circRNAs between OA and control cartilage tissues. The regulatory and functional role of CircSERPINE2 upregulation was examined in OA and was validated in vitro and in vivo, downstream target of Circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
237
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(241 citation statements)
references
References 44 publications
4
237
0
Order By: Relevance
“…miRNA‐103 is also reported to target Sox6 and facilitate OA development . Similarly, multiple types of noncoding RNAs have been investigated and identified by RNA sequencing in diseases with OA progression, including long intergenic noncoding RNAs, antisense RNAs and circular RNAs (circRNAs) . Of note, the wide existence of long non‐coding RNAs (lncRNAs) is accepted in eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNA‐103 is also reported to target Sox6 and facilitate OA development . Similarly, multiple types of noncoding RNAs have been investigated and identified by RNA sequencing in diseases with OA progression, including long intergenic noncoding RNAs, antisense RNAs and circular RNAs (circRNAs) . Of note, the wide existence of long non‐coding RNAs (lncRNAs) is accepted in eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%
“…13 Similarly, multiple types of noncoding RNAs have been investigated and identified by RNA sequencing in diseases with OA progression, including long intergenic noncoding RNAs, antisense RNAs and circular RNAs (cir-cRNAs). [14][15][16][17] Of note, the wide existence of long non-coding RNAs Mechanistically, recent studies show that several lncRNAs or cir-cRNAs, harboring miRNA-binding sites, are capable of functioning as competing endogenous RNAs (ceRNAs) to naturally sequester miRNA away from target mRNA and competitively block the inhibitory impact of miRNA on mRNA. 18 As explained previously, SNHG16 can block the inhibition of miR-205 on Smad2 expression in aortic smooth muscle cell proliferation and migration.…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs are a type of endogenous noncoding RNA that performs very important roles in OA progression 8,36 . Several studies have reported differential expression of circRNAs in OA cartilage and their potential to regulate the vitality and functions of chondrocytes 11,37 . However, little is known about the roles of circRNAs in the articular synovium.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ciRS‐7 promoted the proliferation of chondrocytes in an IL‐1β‐induced OA model via negatively regulating miR‐7 (Zhou, Jiang, et al, ). circRNA‐CER, hsa_circ_0045714, and circSERPINE2 regulate the biosynthesis of the ECM and promote the proliferation of chondrocytes by negatively regulating miR‐136, and activating the miR‐193b/IGF1R and miR‐1271‐5p/ERG axes (Li, Zhang, Xiao, et al, ; Liu, Zhang, et al, ; Shen et al, ). Therefore, abnormally expressed circRNAs in OA‐affected chondrocytes play important roles in the onset and development of OA by inducing or inhibiting chondrocyte apoptosis.…”
Section: Chondrocyte Injuriesmentioning
confidence: 99%